Influencing Parliament to see the importance of genetics - Sanaria Fathulla, Arijit Mukhopadhyay (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Genetic sequencing, especially whole genome sequencing, has become a ground-breaking method for improving public health. While still in development, it has limitations and challenges that all stakeholders need to overcome and adapting to. For integration of these developments into current and future healthcare policies, it is crucial that scientists keep the parliament informed and involved. This is done through the British Society of Genomic Medicine (BSGM) to ensure informed decisions are being made with the public’s interest at the forefront. This interview with Dr Arijit Mukhopadhyay will shed light on the current development of genetics, its integration into public healthcare and potential challenges that arise from it. The Editorial Team would like to thank Dr Arijit Mukhopadhyay for his time and contributions to this article.
Keywords: parliament; genome sequencing; genetic data protection; GDPR; consent; confidentiality; genomics; personalised healthcare; genomic medicine; British Society of Genomic Medicine; genetic counselling; genetics research